Kjerulfs Fjord and Dickson Fjord. Photograpic chart showing no. on photo and general direction taken is denoted by arrow. These correspond to photographs taken by me and sent [to] the American Geographical Society 3/28/32 / Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1932)
Signed: Louise A. Boyd, San Francisco, Calif. March 2nd, 1932.; Black ink on vellum. In the 1930s Louise Arner Boyd funded and led 5 scientific expeditions to East Greenland. This manuscript map was made as part of her 1931 expedition to the Franz Josef Fjord. This trip was a “photographic reconnaissance” in preparation for a more comprehensive 1933 trip. AGS Library staff and students produced a special web application to enable viewing the map with the photos from this expedition. “The Louise Arner Boyd Webmap” - https://uwm.edu/libraries/agsl/agsldata/webapps/boyd/ Grayscale